2017
DOI: 10.2754/avb201786040413
|View full text |Cite
|
Sign up to set email alerts
|

The thermal effect of 2.45 GHz microwave radiation on rat testes

Abstract: The study focused on the effect of microwave radiation at a dose which commonly does not lead to tissue heating, however, in the rat testes it resulted in accumulation of heat. Adult rats were exposed to whole body pulse radiation at a frequency of 2.45 GHz and mean power density of 28 W/m 2 , for 3 h a day for the duration of 3 weeks. Immediately after each irradiation, the body temperature and the testicular temperature were measured in the control and experimental animals. Samples for histological and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The modulated integrity of testis indicates impaired spermatogenesis, apoptosis, and production of spermatozoa with functional and morphological damage. Moreover, male gametes may possess defected DNA [ 36 , 37 , 48 , 52 ]. A decreased number of viable Leydig cells causes alteration of testosterone production.…”
Section: Mode Of Action (Moa)mentioning
confidence: 99%
“…The modulated integrity of testis indicates impaired spermatogenesis, apoptosis, and production of spermatozoa with functional and morphological damage. Moreover, male gametes may possess defected DNA [ 36 , 37 , 48 , 52 ]. A decreased number of viable Leydig cells causes alteration of testosterone production.…”
Section: Mode Of Action (Moa)mentioning
confidence: 99%
“…However, no difference was observed after 10 weeks [17]. It was reported that there wasn't any alteration in the testicular cell apoptosis of 5-weeks-old rats with 2.45 GHz RFR exposure for three weeks (2h/day), but an increase was observed in the testis tissues of 6-weeks-old rats [26]. Interestingly, it has been shown that apoptosis was increased in the offspring rat testis after 900 MHz RFR for 1 h/day through days 13-21 of pregnancy [27].…”
Section: Discussionmentioning
confidence: 91%
“…Many scientific experiments which use animal models have demonstrated the adverse effect of EMR on various tissues and organs (Lee et al 2006;Hanafy et al 2010;El-Bediwi et a. 2011;Almášiová et al 2017;Adebayo et al 2019).…”
mentioning
confidence: 99%